Randomized controlled trial of online interventions for co-occurring depression and hazardous alcohol consumption: Primary outcome results - John A. Cunningham (Elsevier, 2021)
Background and aims: The current trial tested the benefits of offering a brief online intervention for hazardous alcohol consumption along with one for depression among people experiencing both conditions. Methods: Online advertisements were used to recruit people with persistent low mood. Those who also had current hazardous alcohol consumption were identified and invited to take part in the trial (those not eligible were offered access to the online depression intervention). Participants were randomized to an established intervention for depression (MoodGYM; M-only) or to receive MoodGYM plus a brief personalized feedback intervention for hazardous drinking (Check Your Drinking; M + CYD). Participants were followed-up at three and six months. Results: While levels of depression symptoms (p < .001) and hazardous alcohol consumption (p < .001) reduced in both the M-only and the M + CYD groups, there was no difference between groups on drinking (p = .374) or depression outcomes (p = .752). Further, participants who were provided both interventions logged into the intervention website less often (M = 4.1, SD = 3.9) compared to participants only offered the depression intervention (M = 4.9, SD = 5.2), t (986) = 2.47, p = .014. However, there was no significant difference (p > .05) in the number of MoodGYM modules completed between the two groups. Discussion and conclusion: The current trial found no benefit to providing a brief online intervention for hazardous alcohol consumption alongside one for depression among people experiencing these co-occurring disorders. Further, the finding that adding an online intervention for drinking to one for depression led to a small reduction in the number of times the interventions were accessed implies the need for caution when deciding how best to provide online help to those with co-occurring depression and hazardous alcohol consumption.Trial Registration: ClinicalTrials.gov NCT03421080.